Preoperative Serum Prealbumin Level and Adverse Prognosis in Patients With Hepatocellular Carcinoma After Hepatectomy: A Meta-Analysis - Fan, Yu; Sun, Yimeng; Man, Changfeng; Lang, Yakun (Frontiers in Oncology, 2021)
Background Prealbumin is a sensitive indicator of liver function and nutritional status. Objectives This meta-analysis aimed to examine the association of the serum prealbumin level with the prognosis of patients with hepatocellular carcinoma (HCC) undergoing hepatectomy. Methods We comprehensively searched the PubMed, Embase, Wanfang, China Academic Journals (CNKI), and SinoMed databases up to September 1, 2021. Eligible studies should report the association of the serum prealbumin level with prognosis and provide the multivariable-adjusted risk estimates of the outcomes of interest in HCC patients undergoing hepatectomy. Results A total of 11 studies with 7,442 HCC patients were identified and analyzed. Meta-analysis of a fixed effects model showed that a low serum prealbumin level was associated with poor overall survival [hazard ratio (HR) = 1.54, 95% confidence interval (CI) = 1.42–1.68], recurrence-free survival (HR = 1.34, 95% CI = 1.17–1.52), and a higher risk of postoperative hepatic insufficiency (HR = 2.21; 95% CI = 1.36–3.60) in HCC patients. Sensitivity and subgroup analyses confirmed the robustness of low serum prealbumin in predicting poor overall survival. Conclusions This meta-analysis indicated that a low preoperative serum prealbumin level was significantly associated with adverse prognosis in HCC patients undergoing hepatectomy.